Parents’ Rights in Islam and International Laws and Charters - Alhamdi, Musa Abdulrazzeq (Journal of Humanities & Social Sciences, 2022)
The research deals with the parent’s rights in Islam and international laws and covenants. Based on the view of the need for this topic for its close connection with contemporary Muslim life, and the emphasis on the parent’s rights over their children and their performance to the fullest. In addition, to a statement of the precedence of Islam in the field of human rights in general and parental rights in particular, and the role of organizations and bodies in the field of human rights. Furthermore, this topic deals with human rights by adopting the Universal Declaration of Human Rights and the two international covenants. The research aimed to explain human rights in Islam, and to clarify the difference between them and international laws and charters in preserving parental rights. The research used the descriptive research method. The research is composed of an introduction, two chapters, and a conclusion, where the first chapter dealt with the statement of human rights in Islam, and the second the rights of parents in Islam and international laws and covenants. One of the most important results of the research is a statement of the precedence of Islam in the field of human rights, the uniqueness of Islam in preserving the rights of parents, and the absence of any rights for parents stipulated in international laws and covenants.